1989
DOI: 10.1039/p19890000057
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of the higher fungi. Part 24. Cytochalasin N, O, P, Q, and R. New cytochalasins from the fungus Hypoxylon terricola Mill

Abstract: ~~Punctaporonin B, cytochalasin C and D, and five n e w cytochalasins have been isolated from the culture medium and mycelium of the fungus Hypoxylon terricola. Cytochalasin C is the major metabolite. Cytochalasin N is the 5,6-epoxide of cytochalasin C, and cytochalasins 0 and P are t w o epimeric 6-hydroxy analogues. Cytochalasin Q is a 6,7-epoxide and R is a 6,7,13,14-diepoxide. The epoxides formed by cytochalasin C and D are described and the acid-and BF,-induced rearrangement products of cytochalasin N are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 4 publications
1
36
0
Order By: Relevance
“…The 1 H-and 13 C-NMR data of 1 were similar to those of the known cytochalasin Q (3) [6], except for the 13 C-NMR signal of 3 at d(C) 77.8 (C(18)) which was shifted to d(C) 50.7 in 1, suggesting the presence of a CH group in 1 instead of an O-bearing quaternary Catom in 3. This assumption was consistent with the result of the HMQC experiment, which assigned the H-atom at d(H) 3.17 -3.23 (m) to HÀC(18).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…The 1 H-and 13 C-NMR data of 1 were similar to those of the known cytochalasin Q (3) [6], except for the 13 C-NMR signal of 3 at d(C) 77.8 (C(18)) which was shifted to d(C) 50.7 in 1, suggesting the presence of a CH group in 1 instead of an O-bearing quaternary Catom in 3. This assumption was consistent with the result of the HMQC experiment, which assigned the H-atom at d(H) 3.17 -3.23 (m) to HÀC(18).…”
mentioning
confidence: 52%
“…(SCSIO 156) was purified by silica gel (SiO 2 ) and ODS column chromatography (CC), as well as by Sephadex LH-20 CC guided by a brine shrimp (Artemia salina) assay and HPLC/UV to yield the two new cytochalasins 1 and 2, and the four known analogues 3 -6. Compounds 3 -6 were identified on the basis of their spectroscopic data and comparison with those reported [6] [7].…”
mentioning
confidence: 99%
“…-Cytochalasins are a large group of fungal alkaloids with a wide range of biological activities targeting cytoskeletal processes [1]. Some of them exhibited a broad spectrum of activity, including inhibition of HIV-1 protease [2] as well as antibiotic and antitumor activities [3] [4]. During the studies on the production of bioactive metabolites by fungi, it was found that the marine fungus Spicaria elegans produced a number of cytochalasins.…”
mentioning
confidence: 99%
“…isolated from Taxus brevifolia; 1,2 pestalotiopsolide A, teadolidol, and 6-epiteadolidol, highly oxidized caryophyllenes from a Pestalotiopsis sp. endophytic to the bark of Pinus taeda; 3 the 6-hydroxpunctaporonins, antibacterial metabolites from a fungicolous Pestalotiopsis disseminata; 4 fuscoatrol A, a cytotoxic agent from a marine-derived Humicola fuscoatra KMM 4629; 5 the punctaporonins (also named as punctatins), antifungal agents from a coprophilous Poronia punctata; [6][7][8][9][10][11] walleminol and walleminone, two cis-fused iso-caryophyllenes from the toxigenic fungus Wallemia sebi; 12 and Sch 725432, 601253, 601254, and 725434, antifungal agents from Chrysosporium pilosum. 13 During an ongoing search for new bioactive natural products from fungi of unique habitats, we initiated chemical studies of the fungi either inhabiting the fruiting body and larvae of Cordyceps sinensis 14 or its surface soil.…”
Section: Introductionmentioning
confidence: 99%